2013 IEEE/RSJ International Conference on Intelligent Robots and Systems 2013
DOI: 10.1109/iros.2013.6697160
|View full text |Cite
|
Sign up to set email alerts
|

Topological mapping of unknown environments using an unlocalized robotic swarm

Abstract: Abstract-Mapping and exploration are essential tasks for swarm robotic systems. These tasks become extremely challenging when localization information is not available. In this paper, we explore how stochastic motion models and weak encounter information can be exploited to learn topological information about an unknown environment. Our system behavior mimics a probabilistic motion model of cockroaches, as it is inspired by current biobotic (cyborg insect) systems. We employ tools from algebraic topology to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 20 publications
0
37
0
2
Order By: Relevance
“…This sketch includes robust topological information obtained from a minimal amount of sensing. 11 Instead of providing continuous control feedback to the agents, we explore how the insects' natural behavior, modeled using stochastic motion, and weak encounter information in the form of identification of nearby agents can be exploited for mapping. These strategies make up for our platforms' hardware limitations.…”
Section: Mapping and Exploration Strategiesmentioning
confidence: 99%
“…This sketch includes robust topological information obtained from a minimal amount of sensing. 11 Instead of providing continuous control feedback to the agents, we explore how the insects' natural behavior, modeled using stochastic motion, and weak encounter information in the form of identification of nearby agents can be exploited for mapping. These strategies make up for our platforms' hardware limitations.…”
Section: Mapping and Exploration Strategiesmentioning
confidence: 99%
“…We also propose a classification technique to provide a robust quantitative representation of topological features in the data, to construct a map of the environment which will contain only robust features The approach has been analyzed using simulation [6] and experimental data [5] using a swarm robotic platform called the WolfBot [3].…”
Section: System Overviewmentioning
confidence: 99%
“…To minimize control input, we take advantage of the natural behavior of insects in order to estimate a topological model of the environment based only on neighbor-to-neighbor interactions. This approach was first introduced in [6], and was later improved in terms of accuracy and robustness in [5].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the addition of a small buzzer would enable biobotic agents know when they approach another agent. It has been shown that this information can be used to construct a topological map of an unknown environment [8].…”
Section: Introductionmentioning
confidence: 99%